Genotoxicity Assessment and Protective Effect of Anogeissus leiocarpus Roots against Cyclophosphamide-Induced DNA Damage In Vivo - Aku Enam Motto; Povi Lawson-Evi; Aboudoulatif Diallo; Kwashie Eklu-Gadegbeku (Journal of Toxicology)
Background. Belonging to the family of Combretaceae, the roots of Anogeissus leiocarpus are traditionally used to treat diabetes, wounds, infections, pain, and gastrointestinal diseases. To our knowledge, no genotoxicity assessment of the plant was reported. Hence, this study was designed to evaluate the potential genotoxic and protective effects of extract of Anogeissus leiocarpus roots using the micronucleus test on mice bone marrow cells in vivo. Methods. Three different concentrations (250, 500, and 1000 mg·kg−1) of hydroalcoholic extract of roots of A. leiocarpus were administered daily for 7 days per os to mice, and the genotoxicity was induced by the administration ip of cyclophosphamide. Genotoxicity and cytotoxicity were evaluated by counting, respectively, the number of micronucleated polychromatic erythrocytes and polychromatic erythrocytes to total erythrocytes in the bone marrow of mice. Results. The administration of A. leiocarpus did neither increase the ratio of the polychromatic erythrocyte (PCE) nor the frequency of micronucleated PCE (MNPCE) significantly in the bone marrow cells of the mice, compared to the vehicle control animals. However, a significant increase in the incidence of MNPCE in the bone marrow cell of the cyclophosphamide-treated mice was found. Moreover, in the groups treated with the total extract of A. leiocarpus at different doses plus cyclophosphamide, there was a significant decrease p<0.0001 in MNPCEs compared to the positive controls, in a dose-dependent manner. Conclusion. This first finding reports that the extract of A. leiocarpus was neither genotoxic nor cytotoxic. However, it shows a protective effect against the genotoxicity and cytotoxicity induced by cyclophosphamide.